Intronic polymorphisms in genes LRFN2 (rs2494938) and DNAH11 (rs2285947) are prognostic indicators of esophageal squamous cell carcinoma - Wang, Jiru (BMC Med Genet, 2019)
BACKGROUND: Genome wide association study (GWAS) has become the major means to screen for the genetic variants associated with risk and prognosis of different diseases. A recent GWAS has discovered three novel intronic single nucleotide polymorphisms in genes LRFN2 (rs2494938), DNAH11 (rs2285947) and PLCXD2 (rs2399395) that are associated with altered risk of esophageal squamous cell carcinoma (ESCC) among Han Chinese populations. However, the prognostic significance of these variations in ESCC remains unclear. METHODS: To investigate the association of three novel single nucleotide polymorphisms (rs2494938, rs2285947, rs2399395) with the prognosis of ESCC patients, we recruited 287 ESCC patients treated with surgical resection and evaluated the potential significance of the three polymorphisms through Kaplan-Meier survival analysis, log-rank test, and Cox proportional hazards regression models. RESULTS: The ESCC patients carrying genotype AA at rs2494938 had worse survival and genotype GG at 2285947 had better prognosis (Log-rank P = 0.003 and Log-rank P = 0.037, respectively). In addition, rs2494938 at 6p21.1 was independently associated with overall survival of ESCC patients in recessive model [AA vs. GG/GA, HR = 3.12, 95% CI = 1.43–6.83, P = 0.004], rs2285947 at 7p15.3 was independently associated with overall survival of ESCC patients in both dominant model [AA/GA vs. GG, HR = 1.59, 95% CI = 1.02–2.49, P = 0.042] and additive model [AA vs. GA vs. GG, HR = 1.45, 95% CI = 1.05–2.01, P = 0.025]. CONCLUSIONS: This study demonstrated that the polymorphisms rs2494938 at 6p21.1 and rs2285947 at 7p15.3 may serve as independent prognostic biomarkers for ESCC, implying the potential biological role of their related genes (LRFN2 and DNAH11) in the process of ESCC development. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12881-019-0796-9) contains supplementary material, which is available to authorized users.